Spatial vatiability of the dosage of P2O5 and K2O tofertilize in variable rate and in a conventional way in a coffee field - Ferraz, Gabriel Araújo e Silva; da Silva, Fábio Moreira; de Oliveira, Marcelo Silva; Avelar, Rogner Carvalho; Sales, Ronan Souza (Coffee Science - ISSN 1984-3909, 2015)
Fewer studies have been conducted on the spatial variability of inputs dosage in crop field, mainly when it has been performed the comparison between conventional management and precision agriculture management in coffee crop.The aim of this article was to characterize the structure and magnitude of the spatial distribution of soil chemical attributes, and the recommendation of fertilizer application on a coffee field, and map these variables in order to identify the spatial dependence of them. It was also aimed compare the recommendation of fertilize application based on conventional sampling method and based on grid sampling method to demonstrate the advantages of the use of this crop management.. This study was carried out at the Brejão farm in Três Pontas, Minas Gerais state, Brazil. As data base were used phosphorus and potassium sampled conventionally and sampled in a 64 point squared grid. The soil sampling was sent to a soil lab to proceed the analyses of the amount of chemical attributes present in the soil, that allowed to proceed the recommendation of fertilizer application. The analysis of these data by geostatistics tools allowed characterize the spatial variability of phosphorus and potassium, as well as, the dose of P2O5 and K2O recommended by the grid sampling method which allowed creating maps of spatial distribution of these variables. It was possible to identify differences presented in the P2O5 and K20 doses based on the recommendations obtained by the conventional sampling method and by the grid sampling method to precision coffee culture.